Project risk management in the construction industry, comparingtheory and practice - Antonsson, Sebastian; Vojvodic, Boki (My University, 2017)
processes in order to conduct a comparison between their process in practice and processes described in literature. Furthermore, tools and techniques, also found in literature, will be used in the comparison. To conduct this comparison, a frame of reference was made. This frame of reference contains methodologies, standards, handbooks, tools and techniques that are commonly found associated with project risk management. Amongst the methodologies, the most common one is the PMBOK. In the tools and techniques chapter, the SWOT, Monte Carlo simulations and Risk matrices are some of the more common ones. 14 interviews at 11 companies were conducted for data collection. The data showed of risk management is very similar amongst all companies. The processes were often not as structured and developed as the literature suggests and most tools and techniques were not even used. The most common way to do risk management was to conduct workshops where the risks were identified with help from experts. Further, the analysis showed that none of the methodologies from the literature were followed. Parts of it were used but the usage was never associated with any specific methodology. When it comes to the tools and techniques, a few were used quite frequently and some were used but less frequently. Risk matrices were very common and so was Brainstorming as well as Checklists. SWOT and Monte Carlo simulations were used sometimes though not very often. The research showed that the industry is very keen to maintain a simple and easily understandable process. Complex tools such as simulations and advanced systems of qualitative analysis such as Delphi, were not used very much at all. Another common aspect was the lack of clear structure and standardization in the process. Few companies had a standardized process which could be applied in projects. Knowledge transfer was another area where improvement was needed.
Keywords: Samhällsbyggnadsteknik; Civil Engineering